2014
DOI: 10.21273/hortsci.49.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Drying and Shade Effects on Spearmint Oil Yields and Composition

Abstract: ‘Native’ spearmint (Mentha spicata L.) is one of the two most widely grown spearmints in the United States and in other countries. Recent studies demonstrated the feasibility of growing ‘Native’ spearmint as a cash crop for north–central Wyoming. Transportation and energy costs of commercial mint production can be reduced by drying the spearmint in windrows in the field for a few days after harvest and before oil extraction. This method of drying mint has been a common practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…; Zheljazkov et al . ), the volatile compounds and sensory characteristics (Diaz‐Maroto et al . ), and phenolic antioxidants (Orphanides et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Zheljazkov et al . ), the volatile compounds and sensory characteristics (Diaz‐Maroto et al . ), and phenolic antioxidants (Orphanides et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated the effect of drying methods on the yield and composition of the essential oil (Antal et al 2011;Zheljazkov et al 2014), the volatile compounds and sensory characteristics (Diaz-Maroto et al 2003), and phenolic antioxidants (Orphanides et al 2013). Although the chemical composition and bioactivity of dried mints are important, the food industry is mainly interested in consumer acceptability and food safety.…”
Section: Introductionmentioning
confidence: 99%
“…Usually quality of medicinal plant includes moisture content, [30] nutritional value, [27] texture, [31] color, [32] Downloaded by [Selcuk Universitesi] at 17:37 05 February 2015 5 water-soluble proteins, [33] bioactive polyphenols [34] and/or essential oils. [35] Some of quality attributes, such as moisture, texture and color, are measurable in real-time, whereas others are not directly measurable, but could be calculated through relational models. In classical work of Labuza et al [36] it was found that degradation of quality attributes due to non-enzymatic browning, enzymatic activity and lipid oxidation are all non-linear functions of moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil yield of shade dried Ocimum basilicum, Mentha piperita, Origanum vulgare and Origanum onites was the highest [24][25][26]. However, according to a study from United States, neither drying duration nor drying condition had a significant effect on oil yield of Mentha spicata [27]. These drying studies have revealed that the essential oil composition of Lamiaceae plants varied with varying temperature and humidity conditions.…”
mentioning
confidence: 99%